ANALISIS INTERTEKSTUAL MOTIF CERITA MEMOIRS OF A GEISHA KARYA ARTHUR GOLDEN DAN PRIMADONA KARYA NANO RIANTIARNO and Nano Riantiarno’s Primadona) - Anastasia Dewi Aquarini Priyatna Lina Meilinawati Rahayu (SALINGKA, 2015)
This research aims to analyze the intertextual between Primadona and Memoirs of a Geisha. Memoirs of a Geisha with Primadona selected by assumption that some text present inside the other text. The result of this research is the spell out of motif and character. Beside, with the comparison of the similiar aspects, relation the both of Primadona and Memoirs of A Geisha would be explain. This is done by relation between Primadona and Memoirs of A Geisha.